Exchange Rate Policy and Inflation Targeting in Colombia - Hernando Vargas H. (Inter-American Development Bank, Research Department, 2005)
This paper examines Colombia`s experience with an inflation-targeting monetary policy following the abandonment of exchange rate bands in 1999, and two episodes in 2003 and 2004 that deviated from this general behavior. In these episodes, the Central Bank intervened in the forex market on a relatively large scale in order to affect the trend of the exchange rate (managed floating). These episodes are examined to draw lessons and highlight the main challenges facing monetary and forex policy. The rationale for central bank intervention in the forex market in Colombia is then critically discussed. Finally, the paper presents several issues that appear in the debate on Colombian monetary and forex policy and provides an idea of the political context in which monetary policy decisions are made.
Keywords: 330; Wechselkurspolitik; Inflationssteuerung; Geldpolitik; Kolumbien